2016
DOI: 10.1073/pnas.1602764113
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomal arrangement affects single-molecule transcription dynamics

Abstract: In eukaryotes, gene expression depends on chromatin organization. However, how chromatin affects the transcription dynamics of individual RNA polymerases has remained elusive. Here, we use dual trap optical tweezers to study single yeast RNA polymerase II (Pol II) molecules transcribing along a DNA template with two nucleosomes. The slowdown and the changes in pausing behavior within the nucleosomal region allow us to determine a drift coefficient, χ , which characterizes the ability of the enzyme to recover f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The proposed path takes place along the path I with fluctuations of one or two binding sites. This result is in good agreement with the observation of Fitz et al on the dinucleosome template [34]. They have seen a change in the transcription dynamics of the RNA polymerase II, as well as the variation of the opening forces in the force-extension experiment, in the dinucleosome compared to mono-nucleosome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The proposed path takes place along the path I with fluctuations of one or two binding sites. This result is in good agreement with the observation of Fitz et al on the dinucleosome template [34]. They have seen a change in the transcription dynamics of the RNA polymerase II, as well as the variation of the opening forces in the force-extension experiment, in the dinucleosome compared to mono-nucleosome.…”
Section: Discussionsupporting
confidence: 92%
“…This effect might be seen in the transcription rate of the nucleosomal DNA. It has been observed the transcription rate of RNA polymerase II through DNA becomes faster in the presence of two nucleosomes (dinucleosome case) than for mononucleosome [34].…”
Section: Discussionmentioning
confidence: 99%
“…4F). These results suggest that reduced precision in the assembly of the chromatin fiber may contribute to changes in Pol-II speed and splicing fidelity (40,44,48) .…”
mentioning
confidence: 89%
“…Assisting force mode is often used in studies of transcription through nucleosomes, where the tension applied to the upstream DNA ensures there is no transfer of nucleosomes behind the polymerase (22)(23)(24).…”
Section: Basics Of Optical Tweezersmentioning
confidence: 99%
“…They showed that the local nucleosome unwrapping dynamics, and in turn the transcription elongation dynamics, is affected by nucleosomal properties such as the histones modification state, presence of histone tails or the underlying DNA sequence. Recently, our group used optical tweezers to study transcription of Pol II through nucleosomal templates of higher complexity and the influence of nucleosomal geometry on the efficiency of transcription ( Figure 3B) (24). Fitz and colleagues investigated Pol II elongation dynamics along a DNA template with two nucleosomes.…”
Section: Transcription Through Nucleosomesmentioning
confidence: 99%